Sustainable Tourism Development Based on Local Wisdom in Rural Area, Study in Lalos Village, Tolitoli, Indonesia - Mohammad Sawir; Hary Yuswadi; Anastasia Murdyastuti; Pairan Pairan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims to examine the sustainable tourism of local wisdom based tourism development in Lalos Village. The results of the research, integrating local wisdom into tourism development through the active role of the community is the best scenario for realizing sustainable tourism, therefore existing local wisdom must be managed in such a way by local governments, village governments, business actors and local communities so that this potential can become a tourist attraction that can attracting tourists to visit the village, through these visits will have a positive impact on the economy of the local community as well as a form of implementing the concept of community based tourism which will ultimately lead to the preservation local wisdom in accordance with the principles of sustainable tourism development.